Rethinking Greyfields: Using Market-Based Evidence to Assess the Planning of Neighbourhood Renewal Strategies - Carville, Andrew Leigh (Curtin University, 2020)
This thesis will explore the proposition that the current strategies governing medium density infill housing provision applied by some local governments only further contribute to the socio-spatial polarisation of Australian suburbs, and those areas which are seeing increased densities introduced as a catalyst of urban renewal are instead seeing long-held perceptions of the neighbourhood’s character perpetuated, creating further barriers to the reinvention of suburban environments and identities.